Social class and mobility: student narratives of class location in English higher education. Issue 1 (2nd January 2021) - Bathmaker, Ann-Marie
ABSTRACT: This paper explores ways in which university students articulate understandings of their class positions and perceptions of opportunities for social mobility. The promise that participation in higher education (HE) would lead to social mobility for all has been central to the project of widening participation. However, in the twenty-first century, graduate employment opportunities have not kept up with high rates of HE participation, and class divisions have become more visible rather than being reduced. Based on a longitudinal study of undergraduates attending two universities in the city of Bristol, UK at the beginning of the 2010s, this paper uses Anthias' notion of narratives of location to focus on students' awareness of social class and their experience of the dynamics of social difference in HE. The narratives demonstrate ways in which taken-for-granted privileged middle-class entitlement is performed and seen to dominate the social space of the university, from which working-class and other fractions of the middle-classes distance themselves. [Anthias, F. (2004) Social stratification and social inequality: Models of intersectionality and identity. In F. Devine, M. Savage, J. Scott, & R. Crompton (Eds.), Rethinking class. Culture, identities and lifestyles (pp. 24–45). London: Palgrave Macmillan].